Air pollution exposure in early pregnancy and adverse pregnancy outcomes: a register-based cohort study. Issue 2 (5th February 2013) - Olsson, David; Mogren, Ingrid; Forsberg, Bertil
Abstract : Objectives: Our aim was to study the possible associations between exposure to elevated levels of air pollution, ozone (O3 ) and vehicle exhaust (NOx ), during early gestation, and adverse pregnancy outcomes such as pre-eclampsia, preterm birth and small for gestational age. Design: Prospective register-based cohort study. Setting: The Swedish Medical Birth Register includes data on all deliveries during 1998 to 2006 in Greater Stockholm, Sweden. The national Patient Register and the Prescribed Drug Register were used to collect information on maternal asthma. Participants: All singleton pregnancies, conceived at the earliest in August 1997 and at the latest in February 2006, were included, n=120 755. Outcome measures: We studied preterm birth, small for gestational age and pre-eclampsia. Results: 4.4% of pregnancies resulted in a preterm birth. The prevalence of pre-eclampsia was 2.7%. We observed an association between first trimester O3 and preterm birth (OR 1.04, 95% CI 1.01 to 1.08) as well as an association with pre-eclampsia (OR 1.04, 95% CI 1.01 to 1.08), per 10 µg/m 3 increase in O3 . We observed no association between first trimester NOx and adverse pregnancy outcomes. No associations were observed between any of the air pollutants and small for gestational age. Conclusions: Increased levels of O3 during the first trimester increased the risk of pre-eclampsia and preterm birth. Air pollutants did not exhibit any effects on fetal growth restriction. We estimated 1 in every 20 cases of pre-eclampsia to be associated with O3 exposure.